Community-Based Participatory Research with Sexual and Gender Minority Trauma Survivors: Challenges, Solutions, and Recommendations for Future Research - Zabelski, Sasha (Journal of interpersonal violence, 2025)
Research on sexual and gender minority (SGM) and domestic violence/sexual assault (DV/SA) is needed given that SGM people are at elevated risk of experiencing DV/SA and accessing inclusive and affirming services from DV/SA community agencies poses challenges for SGM survivors. Community-based participatory research (CBPR) is emerging as a valuable methodological tool in this area, yet few CBPR studies focus on DV/SA among SGM people. In the current paper, we present a case study of a CBPR study conducted in collaboration with SGM survivors of DV/SA, as well as community stakeholders (i.e., DV/SA agency staff and providers). More specifically, we make six recommendations to address CBPR study challenges specifically focused on SGM DV/SA, including (a) integrating positionality throughout every step of the research process, (b) establishing rapport with community partners early in the process, (c) engaging external experts in conducting research related to SGM DV/SA to enhance community–research partnerships, (d) ensuring diverse identities are represented within the study team, (e) developing clear, co-defined feedback and communication guidelines with a Survivor Advisory Board (SAB), and (f) implementing an SAB engagement/retention plan. We also provide concrete examples from our CBPR case study to illustrate each recommendation. These recommendations may enhance the impact of conducting CBPR that seeks to promote recovery from DV/SA among SGM via practices for sustainable community partnerships and linkage-to-care efforts for SGM survivors.